One of the last unresolved species in Cochlearia sens. trad., West Himalayan C. minutissima, is Eutrema (Brassicaceae) - German, Dmitry A.; Al-Shehbaz, Ihsan A. (Phytotaxa, 2018)
Identity of the hitherto incertae sedis Cochlearia minutissima O.E. Schulz is clarified and its close relationship up to possible conspecificity with Eutrema hookeri Al-Shehbaz & Warwick is established. The combination E. minutissimum is validated.